EMPOWERING TEACHERS THROUGH CONTINUOUS PROFESSIONAL DEVELOPMENT: HOW AN EMPOWERMENT-ORIENTED SCHOOL CULTURE STRENGTHENS TEACHER PROFESSIONALISM? - Mujiyat Mujiyat; Ahmad Suriansyah; Ahmad Alim Bachri; Aslamiah Aslamiah (JURNAL EDUSCIENCE, 2026)
Purpose –This study addresses this gap by examining how an empowerment-oriented school culture strengthens teacher professionalism through CPD in public junior high schools.Methodology – This study employed a qualitative, multi-site case study design across three public junior high schools (SMPN 1, SMPN 3, and SMPN 4 Marabahan) in South Kalimantan, Indonesia. Data were collected through in-depth interviews with principals and teachers, nonparticipant observations of CPD practices, and document analysis of school policies and professional development programs. Data analysis followed Miles and Huberman's interactive model, involving data reduction, data display, and conclusion drawing, with single-site and cross-site thematic analysis to identify patterns and contextual variations.Findings – An empowerment-oriented school culture—characterized by shared values, participatory decision-making, collegial trust, and psychological safety—acts as a key mediating mechanism between CPD and teacher professionalism. When teachers are actively involved in designing and implementing CPD, professional development shifts from isolated training activities to embedded learning practices. This condition enhances teachers' professional agency, reflective practice, instructional innovation, and collaborative learning through professional learning communities, peer mentoring, and reflective supervision.Contribution – This study contributes to the literature by positioning empowerment-oriented school culture as an active mediator linking CPD to teacher professionalism. The findings suggest that empowering school environments is essential for fostering meaningful, context-responsive, and sustainable professional development.